2020
DOI: 10.9734/jeai/2020/v42i930587
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Traditional African Cassava Based Foods: Microorganisms Role in Nutritional and Safety Value

Abstract: Cassava is a drought-tolerant, crop grown in tropical and subtropical areas. For decades the communities of Africa have developed their process to ferment and use cassava. Ikivunde, Inyange, kivunde, Mokopa, Chikwangue, Meduame-M-bong, Cossette, Gari, Attiéké, and Agbelima are the main indigenous fermented cassava based food products from east, west and central Africa respectively. Lactic acid bacteria, yeast, and molds are the main microorganism involve in the fermentation of cassava-based food products and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…During fermentation, grated cassava mash is softened, and there is the disintegration of tissue structure which cause the interaction between the linamarin and the linamarase enzyme located in the cell wall. This leads to the hydrolysis and subsequent production of glucose and cyanohydrins easily broken down to ketone and hydrogen cyanide (Halake & Chinthapalli, 2020). Flibert, Abel, and Aly (2016) reported that fermentation improves food preservation, nutritional value, energy density, and sensory attributes of foods.…”
Section: Introductionmentioning
confidence: 99%
“…During fermentation, grated cassava mash is softened, and there is the disintegration of tissue structure which cause the interaction between the linamarin and the linamarase enzyme located in the cell wall. This leads to the hydrolysis and subsequent production of glucose and cyanohydrins easily broken down to ketone and hydrogen cyanide (Halake & Chinthapalli, 2020). Flibert, Abel, and Aly (2016) reported that fermentation improves food preservation, nutritional value, energy density, and sensory attributes of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Some genera/species of microorganisms that have been reported concerning various cassava fermented foods in Africa are stated in Table 1. During fermentation of cassava products, these microorganisms have been linked to the following roles: cyanide and antinutrients reduction, protein enrichment, food preservation, texture improvement, aroma and flavor change [66][67][68].…”
Section: Optimization Of Cassava Fermentation Process: An Imperative ...mentioning
confidence: 99%
“…Another example of proto-cooperation is the development of a highly efficient fermentation process using a co-culture of L. plantarum SM39, and Propionibacterium freudenreichii DF13 for folate and vitamin B12 production [82,83]. In a recent alkaline fermentation of indigenous African fermented foods, [84,85] The main microorganisms associated with fermentation in some cassava-based food (Adapted from [66]).…”
Section: Optimization Of Cassava Fermentation Process: An Imperative ...mentioning
confidence: 99%
“…Cassava (Manihot esculenta Crantz) is consumed by more than 700 million people around the world and is perhaps one of the highest-value calorie foods in tropical countries (Halake & Chinthapalli, 2020;Ze et al, 2021). Its global production is currently estimated at 168 million tons per year, and Africa alone produces more than half of this amount (Adebayo-Oyetoro et al, 2013;Ze et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Its global production is currently estimated at 168 million tons per year, and Africa alone produces more than half of this amount (Adebayo-Oyetoro et al, 2013;Ze et al, 2021). Cassava roots are considered a nutritionally rich staple and contain almost twice the calories of potatoes (Solanum tuberosum), together with valuable vitamins (folates, thiamin, pyridoxine, riboflavin) and minerals (zinc, magnesium, copper, iron, and potassium) (Halake & Chinthapalli, 2020).…”
Section: Introductionmentioning
confidence: 99%